Users’ perception on ornamentation motif in prayer hall of mosque between highly and less decorated : case study at Alfalah mosque, usj 9 Subang Jaya and As-salam mosque, Puchong Perdana / Norhayati Kassim - Kassim, Norhayati (2015)
Decoration in mosque of Islamic world divided into two categories namely through the architectural composition and applied decoration. This research basically focuses on applied decoration in interior of mosque. Some mosques are highly decorated and some are less decorated. However certain mosques are left undecorated. Decorating of mosque was intended to serves certain function. One of it is to create the feeling of Remembering Allah. At the same time certain Islamic scholars are highlighted that excessive decoration in mosque can cause bad effect such as distracting users’ attention. Therefore, this research intend to investigate how feeling of Remembering can be achieved and whether ornamentation motif in mosque distracting users through their perception. This research involved mix-method approach and two mosque as case study site as comparison. Quantitative is main method of this research where survey using questionnaire as instrument was distributed to users of both mosque. While, qualitative method involved face to face interview with imam, mosque community members, mosque organization leader as well academician. Based on site observation and initial interview with interior designers 4 variables found to differentiate between highly and less decorated mosque. There are namely color, quantity, position and typology of ornamentation motif. Result of research found that the most ornamentation that can relate users with remembering Allah is calligraphy. While in term of color, soft and light color can create feeling of serenity and calmness instead of bold and vibrant color.